Evaluating Federated Learning Scenarios: Impact of Basic Parameters and Realistic Communication in Testbeds - Meyer, Bruno H.; Pozo, Aurora; Nogueira, Michele; Zola, Wagner M. Nunan (Anais da Escola Regional de Alto Desempenho da Região Sul (ERAD-RS); 2025: Anais da XXV Escola Regional de Alto Desempenho da Região SulDO - 10.5753/eradrs.2025.6837, 2025)
This paper evaluates Federated Learning in different scenarios to identify differences between simulations and hardware. The scenarios include the MENTORED Testbed with x86 nodes, an experimental cluster with aarch64 architectures, and a server simulating FL using Docker.